Controlling upconversion in emerging multilayer core–shell nanostructures: from fundamentals to frontier applications. (21st February 2022) - Liu, Songbin; Yan, Long; Huang, Jinshu; Zhang, Qinyuan; Zhou, Bo
Abstract : This review presents a summary and discussion on the design, synthesis and optical manipulation of the recently emerged lanthanide-based multilayer core–shell (MLCS) nanostructures together with their diversities of frontier applications. Abstract : Lanthanide-based upconversion nanomaterials have recently attracted considerable attention in both fundamental research and various frontier applications owing to their excellent photon upconversion performance and favourable physicochemical properties. In particular, the emergence of multi-layer core–shell (MLCS) nanostructures offers a versatile and powerful tool to realize well-defined matrix compositions and spatial distributions of the dopant on the nanometer length scale. In contrast to the conventional nanomaterials and commonly investigated core–shell nanoparticles, the rational design of MLCS nanostructures allows us to deliberately introduce more functional properties into an upconversion system, thus providing unprecedented opportunities for the precise manipulation of energy transfer channels, the dynamic control of upconversion processes, the fine tuning of switchable emission colours and new functional integration at a single-particle level. In this review, we present a summary and discussion on the key aspects of the recent progress in lanthanide-based MLCS nanoparticles, including the manipulation of emission and lifetime, the switchable multicolour output and the lanthanide ionic interactions on the nanoscale. Benefitting from the multifunctional and versatile luminescence properties, the MLCS nanostructures exhibit great potential in diversities of frontier applications such as three-dimensional display, upconversion laser, optical memory, anti-counterfeiting, thermometry, bioimaging, and therapy. The outlook and challenges as well as perspectives for the research in MLCS nanostructure materials are also provided. This review would be greatly helpful in exploring new structural designs of lanthanide-based materials to further manipulate the upconversion phenomenon and expand their application boundaries.